1995
DOI: 10.1016/0248-4900(96)85281-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of maitotoxin on calcium entry and ciliary beating in the rabbit ciliated tracheal epithelium

Abstract: The marine toxin maitotoxin (MTX) induces stimulation of ciliary beating in primary cultures of rabbit tracheal epithelial cells. The response is time- and concentration-dependent. External calcium is an absolute requirement, although at a very low concentration (50 microM for maximal effect). Pretreatment of the cells with MTX induces an early (5 min) and sustained ( > or = 24 h) homologous desensitization. The response to MTX is strongly inhibited by trifluoperazin (an inhibitor of Ca-calmodulin-dependent en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…But neither calmodulin inhibitors nor phosphatase inhibitors changed the kinetic relationship between [Ca 2+ ] i and CBF. Okadaic acid has previously failed to inhibit a CBF increase upon Ca 2+ entry into rabbit airway epithelial cells (Venant et al 1995). Despite their utilization in unicellular organisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…But neither calmodulin inhibitors nor phosphatase inhibitors changed the kinetic relationship between [Ca 2+ ] i and CBF. Okadaic acid has previously failed to inhibit a CBF increase upon Ca 2+ entry into rabbit airway epithelial cells (Venant et al 1995). Despite their utilization in unicellular organisms (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Maitotoxins may stimulate phospholipid breakdown in the cell membrane due to activation of phospholipase C (Venant et al, 1995). Necrotic cell death is partially mediated by calpain (neutral cytosolic cysteine protease present in central nervous system) activation (Zhao et al, 1999 (Daly et al, 1995) Microcystins (e.g.…”
Section: Clostridium Perfringensmentioning
confidence: 99%
“…MTX activation of Phospholipase C (PLC) did not appear to involve Gi or Go, because the response to the toxin was insensitive to pertussis toxin (Gusovsky, Yasumoto, and Daly 1989). Venant et al (1994) also reported that MTX induces calcium uptake in primary cultures of rabbit epithelial cells, and that this activation may not be linked to a trimeric G-protein. Instead, this group proposed that the action of the toxin might result from activation of another type of PLC such as PLC-°, whose activation is dependent on phosphorylation by tyrosine kinase.…”
Section: Figurementioning
confidence: 99%